Association between Objective and Subjective Sleep Parameters with Postural Control Responses among Brazilian Schoolteachers - Soares de Almeida Ciquinato, Daiane; Lozza de Moraes Marchiori, Luciana; Aparecida Bazoni, Jessica; Eumann Mesas, Arthur; Alexandre da Silva, Rubens (Sleep Science, 2023)
Objective To investigate the impact of sleep quality on postural control in teachers.Methods Cross-sectional study with 41 schoolteachers (mean age 45.7 ± 10.4 years). Sleep quality was assessed in two ways: objectively (through actigraphy), and subjectively (through the Pittsburgh Sleep Quality Index). Postural control was assessed in an upright posture during 3 trials of 30s (bipedal and semitandem stances in rigid and foam surfaces with eyes open) with a period of rest across trials, on a force platform, based in the center of pressure measurements in the anteroposterior and mediolateral directions.Results The prevalence of poor sleep quality in this study sample was 53.7% (n = 22). No differences were found between Poor and Good sleep in the posturographic parameters (p > 0.05). Although, there was moderate correlation between postural control in the semitandem stance and subjective sleep efficiency for center of pressure area (rs = -0.424; p = 0.006) and amplitude in anteroposterior direction (rs = -0.386; p = 0.013).Discussion There is correlation between poor sleep quality and postural control in schoolteachers, as sleep efficiency decreases, postural sway increases. Poor sleep quality and postural control were investigated in other populations, but not in teachers. Several factors such as work overload, insufficient time for physical activities, among others, can contribute to a worse perception of sleep quality, as well as deterioration in postural control. Further studies with larger populations are needed to confirm these findings.
Keywords: postural balance; sleep; school teachers